SysEnade - Análise das questões de provas do Enade organizadas pelos temas abordados - Lima, Priscila da Silva Neves (2019)
This article aims to presents a methodology for classification and analysis of National Assessment of Student Achievement (ENADE) exams by themes within the domain knowledge of the test. Exam questions are automatically classified using dictionaries that represent these themes. The mechanism then separates the student’s results by theme, obtaining a grade for each theme, and generates reports that provide a better understanding of the structure of the exam and the student’s outcome. A prototype has been implemented and tested with Enade Computer Science exams. The results showed the methodology allows to identify areas where students excel, and how the exam reflects the structure of the course.